2021
DOI: 10.1186/s40623-021-01376-6
|View full text |Cite
|
Sign up to set email alerts
|

Model-based reproduction and validation of the total spectra of a solar flare and their impact on the global environment at the X9.3 event of September 6, 2017

Abstract: We attempted to reproduce the total electron content (TEC) variation in the Earth's atmosphere from the temporal variation of the solar flare spectrum of the X9.3 flare on September 6, 2017. The flare spectrum from the Flare Irradiance Spectral Model (FISM), and the flare spectrum from the 1D hydrodynamic model, which considers the physics of plasma in the flare loop, are used in the GAIA model, which is a simulation model of the Earth's whole atmosphere and ionosphere, to calculate the TEC difference. We then… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In fact, the photoionization and photo-dissociative ionization cross sections corresponding to the EUV emissions employed in GAIA are relatively large (see Fig. 5 of Watanabe et al 2021). Furthermore, the timescale of electron recombination in the D and E regions of the ionosphere ionized by soft X-ray emission and high-temperature coronal line emission is a few minutes, whereas the timescale of recombination in the F region ionized by low-temperature coronal line emissions is, on average, hours, suggesting that low-temperature coronal line emissions are important for TEC enhancement (Zhang et al 2011).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In fact, the photoionization and photo-dissociative ionization cross sections corresponding to the EUV emissions employed in GAIA are relatively large (see Fig. 5 of Watanabe et al 2021). Furthermore, the timescale of electron recombination in the D and E regions of the ionosphere ionized by soft X-ray emission and high-temperature coronal line emission is a few minutes, whereas the timescale of recombination in the F region ionized by low-temperature coronal line emissions is, on average, hours, suggesting that low-temperature coronal line emissions are important for TEC enhancement (Zhang et al 2011).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…TEC distribution was obtained by inputting the solar flare spectrum obtained from the above study into GAIA. By comparing with the observed TEC distribution, it was found that the effective wavelength for increasing TEC is around 30 nm (Watanabe et al 2021).…”
Section: X-rays and Extreme Ultraviolet Emissionsmentioning
confidence: 98%
“…Nishizuka et al (2021) reported the operational solar flare prediction model using Deep Flare Net. Watanabe et al (2021) reported the model-based reproduction and validation of the total spectra of a solar flare and their impact on the global environment. Nishimoto et al (2021) examined the computed extreme ultraviolet emission spectra during solar flares.…”
mentioning
confidence: 99%